2020
DOI: 10.1039/d0cc06072k
|View full text |Cite
|
Sign up to set email alerts
|

Multiple crystal phases of intermetallic tungsten borides and phase-dependent electrocatalytic property for hydrogen evolution

Abstract: Four stoichiometric W-B intermetallic phases, including W2B, WB, WB2 and WB3, are synthesized, and their hydrogen-evolution electrocatalytic properties and electronic structures are investigated comparatively. The electrocatalytic activity for the hydrogen...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…The Mo 2 NiB 2 displayed the lowest overpotential for HER among all non‐precious metal borides in both basic and acidic solution and good performance stability, which was related with the intrinsic activity of the catalytic sites. Previous investigations reported that the HER active sites of metal borides derived from their intrinsic surface rather than the derivatives of metal borides, [ 12,15 ] which were different from the OER active sites, above discussed. In order to clarify the exact nature of catalytic sites for HER, we performed XPS analysis after HER (Figure S18, Supporting Information), which showed a negligible change for the Mo3d and Ni2p spectra, compared to use with fresh Mo 2 NiB 2 , but with a slight increase of B 0 ratio in the B1s spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mo 2 NiB 2 displayed the lowest overpotential for HER among all non‐precious metal borides in both basic and acidic solution and good performance stability, which was related with the intrinsic activity of the catalytic sites. Previous investigations reported that the HER active sites of metal borides derived from their intrinsic surface rather than the derivatives of metal borides, [ 12,15 ] which were different from the OER active sites, above discussed. In order to clarify the exact nature of catalytic sites for HER, we performed XPS analysis after HER (Figure S18, Supporting Information), which showed a negligible change for the Mo3d and Ni2p spectra, compared to use with fresh Mo 2 NiB 2 , but with a slight increase of B 0 ratio in the B1s spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Second, the metal borides can be much easier oxidized into metal oxides/hydroxides than the nitrides and sulfides, which are the final catalysts for OER. By far, a variety of highly crystalline intermetallic borides, such as WB 2 , [ 12 ] MoB 2 , [ 13 ] Mo 2 B 4 , [ 14 ] and VB [ 15 ] have been developed for HER in both acidic and basic solutions. Nickel borides‐based catalysts, such as amorphous nickel boride (Ni x B), [ 16 ] nickel boride‐hydroxide nanoparticles (Ni 2 B/Ni(OH) x ) [ 17 ] and Ni‐ZIF/Ni‐B nanosheets, [ 18 ] have been found to show promising activity for OER.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the values of integrating -COHP (-ICOHP) up to the Fermi level can be used as a descriptor for quantitative evaluation of the strength of N 2 adsorption 24 and the values were −4.741 and −4.902 for WB 2 (001) and Fe-WB 2 (001), respectively. The more negative value of W-N ads in Fe-WB 2 (001) indicates the stronger N 2 adsorption between N ads and the Fe-WB 2 (001) surface, 25 which is more conducive to the transfer of substrate electrons to nitrogen (Fig. S7, ESI †) and facilitates the subsequent hydrogenation process.…”
Section: Resultsmentioning
confidence: 99%
“…and have also been recently reported. [70,102,122,[178][179][180][181][182][183][184] In general, precious-metal-based TMBs always exhibit higher HER activity than that of non-noble-metal-based TMBs. Indeed, some noble-metal-based borides have recently been designed and have catalyzed the HER with Pt-like activity.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 99%